(untitled) (European Journal of Economics, Finance and Business Development, 2024)
The development of the world economy will be influenced by cognitive factors (from the Latin word “cognition” — “knowledge”, “thinking”) and the economy of economy, production based on nanotechnology and biotechnology. This leads to a sharp increase in the amount of information required to develop and make management decisions in the economy.